Teachers' Creativity in Designing Innovative Entrepreneurship-Based Learning in Vocational High Schools - A. Ramli Rasyid; Taufiq Natsir; Muhammad Asriadi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This Community Service Program (PKM) aims to enhance teachers' creativity in designing innovative, entrepreneurship-based learning at SMK Negeri 1 Tinambung. Situation analysis revealed that the school’s teaching methods remain predominantly conventional, limiting student engagement and motivation, which is essential for modern educational demands. To address this, the proposed solutions included teacher creativity enhancement training, assistance in integrating technology into teaching, and the formation of an innovative learning community. The program successfully increased teachers' knowledge and skills in applying entrepreneurship-based learning strategies and educational technology, despite time and facility limitations. Results indicate improved teacher ability to create relevant, inspiring lessons, positively impacting students’ learning motivation.